The Impact of Financial Literacy on Access to Finance: Does Risk Attitude Matter? - Addo, Selma Dzifa; Asante, Joseph (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
The purpose of the paper was to assess the effect of financial literacy on the access to finance of SMEs. Thus, the study examined the effect of financial literacy on SMEs’ access to finance in developing economies. Data for the study was collected from SME owners/managers in Ghana through questionnaires. 396 questionnaires were analyzed. The Partial Least Square Structural Equation Modelling (PLS-SEM) was used as the main analytical tool. The study found a significant positive association between financial literacy and access to finance. Financial literacy also had a positive significant effect on risk attitude, whereas the link between risk attitude and access to finance was also found significant. Again, the study showed that risk attitude matters in the nexus between financial literacy and access to finance, as it was found to mediate the link between financial literacy and access to finance. Our findings affirm the dual process theory of reasoning where an entrepreneur’s decision to access finance is guided by two systems of thinking: the automatic unconscious system based on their risk attitude, and the deliberate conscious system where different considerations and models are weighed up based on their financial literacy, both of which serves to magnify or dampen rational decision-making to access business financing. The findings also affirm the Knowledge base view theory (KBV) that, financial literacy is a special strategic asset organizations can use to obtain a competitive advantage over competitors. Practically, SMEs will be encouraged to improve their financial literacy and risk attitude skills.